2020
DOI: 10.1038/s41467-020-14331-y
|View full text |Cite
|
Sign up to set email alerts
|

Nr4a1 suppresses cocaine-induced behavior via epigenetic regulation of homeostatic target genes

Abstract: Endogenous homeostatic mechanisms can restore normal neuronal function following cocaine-induced neuroadaptations. Such mechanisms may be exploited to develop novel therapies for cocaine addiction, but a molecular target has not yet been identified. Here we profiled mouse gene expression during early and late cocaine abstinence to identify putative regulators of neural homeostasis. Cocaine activated the transcription factor, Nr4a1, and its target gene, Cartpt, a key molecule involved in dopamine metabolism. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
103
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 70 publications
3
103
2
Order By: Relevance
“…Although a number of studies have previously shown that discrete ensembles of MSNs are activated as a consequence of cocaine exposure (7,20,37), the present findings expand on this body of work in several important ways. For example, while our data are congruent with previously reported IEG changes (e.g., Fosb, Egr1, and Nr4a1) in response to drug experience (7,20,38), our results extend this work by revealing hundreds of other cocaine-induced gene changes in transcriptionally defined populations, many of which have not been previously explored in the context of addiction. Cell type-specific transcriptional profiling with snRNA-seq revealed that cocaine activates a subset of Drd1-MSNs and Drd2-MSNs, but this effect was more robust in the Drd1-MSN population-both in terms of number a public web browser where the datasets produced by these experiments can be viewed (available via day-lab.org/resources).…”
Section: Discussionsupporting
confidence: 92%
“…Although a number of studies have previously shown that discrete ensembles of MSNs are activated as a consequence of cocaine exposure (7,20,37), the present findings expand on this body of work in several important ways. For example, while our data are congruent with previously reported IEG changes (e.g., Fosb, Egr1, and Nr4a1) in response to drug experience (7,20,38), our results extend this work by revealing hundreds of other cocaine-induced gene changes in transcriptionally defined populations, many of which have not been previously explored in the context of addiction. Cell type-specific transcriptional profiling with snRNA-seq revealed that cocaine activates a subset of Drd1-MSNs and Drd2-MSNs, but this effect was more robust in the Drd1-MSN population-both in terms of number a public web browser where the datasets produced by these experiments can be viewed (available via day-lab.org/resources).…”
Section: Discussionsupporting
confidence: 92%
“…From our datasets we also found several genes implicated in cocaine action based on previous literature. From HC Acute cocaine exposure, we found upregulation of the immediate-early genes (IEGs) Nr4a1 and Fos [ 14 , 22 26 ]. Repeated home cage cocaine exposure (HC Chronic) upregulated expression of several genes that are increased within the midbrain of human chronic cocaine users ( Cdnk1a, Nfkbia and Fosb) [ 27 ] or by chronic cocaine in preclinical mouse studies ( Fosb ) [ 24 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with other studies examining HDAC activity in the NAc which have shown to regulate aspects of cocaine and cue-primed reinstatement and incubation of craving in rats, but not cocaine reinforcement ( Taniguchi et al, 2017 ; Li et al, 2018 ). Moreover, our impaired cocaine seeking effects presents a possible upstream mechanism for work from the Heller lab, where CRISPR-mediated overexpression of an HDAC3 target, Nr4a1, similarly resulted in decreased cocaine-seeking following cocaine IVSA ( Carpenter et al, 2020 ). It is possible that the contrasting effects of CPP versus cocaine seeking from our D1R-HDAC3 manipulation, may reflect differences in HDAC3-dependent mechanisms when cocaine is self-administered, as physiological differences in experimenter-administered and cocaine-self administration are reported ( Larson et al, 2011 ; McCutcheon et al, 2011 ; Anderson et al, 2018 ).…”
Section: Discussionmentioning
confidence: 96%
“…These cocaine-induced changes in Nr4a1 expression may be mediated by changes in H4K8Ac. HDAC3's deacetylase activity thus may be critical in driving downstream functions of Nr4a1, as Nr4a1 is critical in regulating both memory formation and cocaine action ( Kwapis et al, 2019 ; Carpenter et al, 2020 ). Interestingly, although HDAC3 occupancy was reduced at the Fos promoter, no changes in H4K8Ac were detected.…”
Section: Discussionmentioning
confidence: 99%